Flow patterns in shallow rectangular reservoirs with open channel inlet or pipe flow inlet at various depths: An experimental study - El Mehdi Chagdali; Kamal El Kadi Abderrezzak; Sébastien Erpicum; Cédric Goeury; Matthieu Secher; Benjamin Dewals (International Journal of Sediment Research)
This study experimentally assesses the influence of varying the inlet boundary condition on the flow patterns in rectangular shallow reservoirs. Two types of inlet boundary conditions were compared: a free surface inlet channel, and a pressurized circular inlet jet positioned at three different elevations over the flow depth (centroid of the inlet jet situated at 25%, 50%, or 75% of the flow depth). The outlet boundary condition was a free surface channel in all cases. Twenty-two experiments were done with two distinct reservoir lengths (length-to-width ratios of 1.1 and 2.0) and three hydraulic boundary conditions (Froude numbers of 0.14, 0.16, and 0.21). Velocity fields were measured with Large-Scale Particle Image Velocimetry (LSPIV) at the surface, and with an Acoustic Doppler Velocity Profiler (ADVP) at several cross sections. The flow patterns are greatly influenced by the inlet boundary condition and the reservoir geometry, but to a lesser extent by the hydraulic boundary condition. For an inlet circular jet located near the reservoir bottom, an unstable flow type, changing over time in a chaotic manner, was observed regardless of the reservoir length and of the inlet flow rate. The same type of unstable flow pattern was observed for a relatively long reservoir and the lowest tested flow rate, irrespective of the vertical positioning of the inlet jet. In all other tested configurations, a steady reattached jet was found in the reservoir equipped with a pressurized inlet jet. In addition to providing new knowledge on flow patterns in shallow reservoirs with an inlet jet, the experimental data presented here will prove valuable for evaluating flow computational models.